Reader Response: Demythologising the Text - Brown, Schuyler (New Testament studies, 1988)
The Greek word έξήγησις means ‘explanation’ or ‘interpretation’. When applied to the Bible, it would appear to mean ‘explication de texte’. However, Biblical exegetes are often in the habit of contrasting what they do with ‘eisegesis’, i.e. the imposition of ‘subjective’ meanings onto the text. This contrast suggests that the meaning derived by exegesis is gotten ‘out of’ the text, where it is thought to reside, by means of the ‘correct’ exegetical methods, of which the exegete is the master. Like Philip the Evangelist, the exegete responds to the plea for help implied in the reader's befuddled question, ‘How can I [understand], unless someone guides me?’ (Acts 8.31).